IPO Pricing with Bookbuilding and a When-Issued Market - Aussenegg, Wolfgang; Pichler, Pegaret; Stomper, Alex (Journal of Financial and Quantitative Analysis, 2006)
We study IPO pricing in Germany to determine whether when-issued trading provides information that is useful for setting IPO offer prices, and whether such trading supplants bookbuilding as a source of information. We find that when-issued trading reveals relevant information for pricing IPOs, and that, once when-issued trading has begun, bookbuilding is not a source of costly information for pricing. But bookbuilding does not appear to be fully supplanted as a source of pricing information. We find evidence consistent with bookbuilding being used to gather information prior to the onset of when-issued trading.